2012
DOI: 10.1088/1468-6996/13/6/064211
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stiffness affects skeletal myoblast differentiationin vitro

Abstract: To maximize the therapeutic efficacy of cardiac muscle constructs produced by stem cells and tissue engineering protocols, suitable scaffolds should be designed to recapitulate all the characteristics of native muscle and mimic the microenvironment encountered by cells in vivo. Moreover, so not to interfere with cardiac contractility, the scaffold should be deformable enough to withstand muscle contraction. Recently, it was suggested that the mechanical properties of scaffolds can interfere with stem/progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 50 publications
4
39
0
Order By: Relevance
“…The local mechanical interactions between cells and their microenvironment regulate cell shape, organization and differentiation of the different tissues [95,96] as can be observed in (Fig. 5) [97][98][99][100][101][102][103][104][105][106][107]. This observation is true in the natural environment as well as in artificial 3D structures.…”
Section: Mechanical Properties Of Scaffoldsmentioning
confidence: 71%
See 1 more Smart Citation
“…The local mechanical interactions between cells and their microenvironment regulate cell shape, organization and differentiation of the different tissues [95,96] as can be observed in (Fig. 5) [97][98][99][100][101][102][103][104][105][106][107]. This observation is true in the natural environment as well as in artificial 3D structures.…”
Section: Mechanical Properties Of Scaffoldsmentioning
confidence: 71%
“…[4,[97][98][99][100][101][102][103][104][105][106][107] On the bottom, typical substrate materials used for cell culturing. Polyacrylamide (PAM); Polydimethylsiloxane (PDMS); Polystyrene (PS).…”
Section: Fig (5)mentioning
confidence: 99%
“…One of the great advantages of PCL over other temperature-responsive polymers is that surface properties such as wettability and charge are independent of temperature. We have previously shown how mechanical properties of PCL influence cell behavior using MSCs [21], skeletal myoblasts [22], fibroblasts [20], and neonatal cardiomyocytes [23,24]. We have also fabricated shape-memory substrates from PCL because the crosslinked PCL offers reversible crystallizable regions that can fix a temporary shape and have dualshape capability, showing a shape memory effect [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that substrate stiffness affects skeletal myoblast differentiation. 38 Myoblasts differentiate optimally on softer substrates with tissue-like stiffness. 39 The thinner fibers are less structurally stiff and therefore more similar to tissue stiffness (elastic modulus of muscle tissue ~ 5-15 kPa) 40 than the thicker fibers.…”
mentioning
confidence: 99%
“…This could be related to diminished cell proliferation or migration, both regulated by decorin. 38,50 This in turn affects the formation of myotubes causing less and thinner myotubes to be present in PCL scaffolds.…”
mentioning
confidence: 99%